An Active Millimeter-Wave Imager Based on MIMO-SAR Scheme - Chen, Xu; Zeng, Yang; Yang, Qi; Deng, Bin; Wang, Hongqiang (Journal of infrared, millimeter and terahertz waves, 2021)
In this article, an active millimeter-wave imager based on multiple-input multiple-output synthetic aperture radar (MIMO-SAR) scheme is presented. In order to achieve two-dimensional (2-D) synthetic aperture, a one-dimensional (1-D) high-precision mechanical scanning frame is used to combine with a self-designed 1-D millimeter-wave sparse MIMO array. The hardware composition of the presented imager is introduced in detail. In addition, a new operation method of transmitting and receiving based on the designed 1-D millimeter-wave sparse MIMO array is proposed. Different from the full-channel mode, a minimum number of transmitters and receivers is required in our method to make the equivalent phase centers (EPCs) evenly distributed while covering the whole array aperture. In this way, the amount of the echo data can be significantly reduced, and the real-time imaging can be realized by applying fast imaging algorithms. Experimental results show that the proposed imager and the corresponding array operation method perform well in high-resolution imaging and concealed object detection.